Pengaruh Komunikasi Terhadap Kinerja Karyawan Pada PT. Jamkrindo Cabang Sorong - Bria, Aprinda Pricilia; Muskita , Susana M. W (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to analyze the influence of communication on employee performance at PT Jamkrindo Sorong Branch. Communication is a key element in an organization that functions to convey information, instructions, and feedback that has an impact on the effectiveness and efficiency of employee work. The research method used is a quantitative approach with data collection through questionnaires and using SPSS software which is distributed to all employees at PT Jamkrindo Sorong Branch. The research sample amounted to 13 respondents. The results of the study show that effective communication has a significant effect on improving the performance of employees at apt jamkrindo Sorong Branch.